2017
DOI: 10.1177/2167702617727559
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Negative Parenting Mediate Changes in Children’s Autonomic Responding Following a Preschool Intervention for ADHD

Abstract: Abnormal patterns of sympathetic- and parasympathetic- linked cardiac activity and reactivity are observed among externalizing children, and mark deficiencies in central nervous system regulation of behavior and emotion. Although changes in these biomarkers have been observed following treatment, mechanisms remain unexplored. We used MEMORE-a new approach to analyzing intervening variable effects-to evaluate improvements in parenting as mediators of changes in SNS- and PNS-linked cardiac activity and reactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 65 publications
4
39
1
1
Order By: Relevance
“…The current analysis suggests that of the parents in the PFR group, those who benefited most from PFR—the parents who subsequently engaged in the most sensitive, responsive parenting—had children who were most likely to show the pattern of RSA reactivity that is typical of normatively developing young children. Thus, this moderation effect could be seen as consistent with the mediation effects reported in prior non‐experimental studies showing that changes in parenting behavior following an intervention statistically accounted for changes in children's parasympathetic activity from pre‐ to post‐intervention (Bell et al., ; Graziano et al., ). Why greater sensitivity and responsiveness would predict stronger RSA reactivity in children of parents who did not receive the PFR intervention is less clear.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The current analysis suggests that of the parents in the PFR group, those who benefited most from PFR—the parents who subsequently engaged in the most sensitive, responsive parenting—had children who were most likely to show the pattern of RSA reactivity that is typical of normatively developing young children. Thus, this moderation effect could be seen as consistent with the mediation effects reported in prior non‐experimental studies showing that changes in parenting behavior following an intervention statistically accounted for changes in children's parasympathetic activity from pre‐ to post‐intervention (Bell et al., ; Graziano et al., ). Why greater sensitivity and responsiveness would predict stronger RSA reactivity in children of parents who did not receive the PFR intervention is less clear.…”
Section: Discussionsupporting
confidence: 85%
“…This is a serious limitation of socialization theory and research, because even with repeated-measures longitudinal analyses (Kennedy, Rubin, Hastings, & Maisel, 2004;Miskovic et al, 2009;Perry et al, 2014), other unmeasured variables such as pre-existing individual differences, or genetic relatedness between parents and children, may account for the apparent contributions of parenting behavior to children's baseline or reactive parasympathetic activity. Even studies that have measured preschoolers' parasympathetic regulation before and after a parent-training program and shown that changes in parenting behavior mediate the effects of the intervention on children's RSA (Bell, Shader, Webster-Stratton, Reid, & Beauchaine, 2018;Graziano, Bagner, Sheinkopf, Vohr, & Lester, 2012) cannot make a strong causal inference about parenting effects if they fail to include a comparative control group and random assignment to groups.…”
Section: Maltreatment Socialization and Parasympathetic Regulationmentioning
confidence: 99%
“…For example, a meta‐analysis showed that family and parent interventions stimulated the normalization of cortisol reactivity among groups of at‐risk children aged 0–18 years (Slopen, McLaughlin, & Shonkoff, 2013). Specific evidence comes from several different individual RCTs on at‐risk groups and subgroups of maltreated and foster children (Bell, Shader, Webster‐Stratton, Reid, & Beauchaine, 2018; Cicchetti, Rogosch, Toth, & Sturge‐Apple, 2011; Dozier, Peloso, Lewis, Laurenceau, & Levine, 2008; Fisher, Van Ryzin, & Gunnar, 2011). Another RCT of a family‐oriented psychosocial intervention among African‐American youths, found intervention‐induced reductions in blood inflammation levels in adolescents, a proxy for improved stress regulation (Miller, Brody, Yu, & Chen, 2014).…”
Section: Flipping the Methylation Switchmentioning
confidence: 99%
“…Although some have attributed low RSA among depressed samples to antidepressant treatment including tricyclics and SSRIs (selective serotonin reuptake inhibitors; O'Regan, Kenny, Cronin, Finucane, & Kearney, 2015), unmedicated, physically healthy individuals with major depression also exhibit lower than normal RSA (Kemp, Quintana, Felmingham, Matthews, & Jelinek, 2012). Emerging evidence suggests that, for at least some disorders, low resting RSA is state dependent and often improves between illness episodes and following effective psychosocial interventions (e.g., Bell, Shader, Webster-Stratton, Reid, & Beauchaine, 2018;Bylsma, Salomon, Taylor-Clift, Morris, & Rottenberg, 2014).…”
mentioning
confidence: 99%